Potassium Chloride Performance as Expansion Inhibitor Agent in Clayey Soils with Mineralogical Content of Montmorillonite - Torres, Juan Diego (2024)
Expansive soils are a type of problematic soil that, due to its physicochemical characteristics, tends to undergo volumetric changes in its internal molecular structure when experiencing alterations in its moisture content. The relevance of his study lies in the numerous structural damages registered worldwide as a result of this phenomenon. Although there are agents for its stabilization, the current environmental trend leads to the search for alternative sustainable materials that guarantee favorable results in inhibiting its expansive character. In this sense, this research aims to evaluate the contribution of potassium chloride in the expansive parameters of a soil sample with mineralogical content of montmorillonite extracted from the locality of Talara, Peru. For this purpose, free swell tests and swelling pressure tests were performed on samples with dosages of 0, 2, 4, 6, and 8% potassium chloride by weight, obtaining as main result a significant reduction in the expansion potential.